Research Trends and Future Works on Student Creativity in the Context of Sustainability: A Bibliometric Analysis - Dindin Nasrudin; Agus Setiawan*; Dadi Rusdiana; Liliasari Liliasari (Universitas Syiah Kuala, 2023)
Education at the university level must provide learning experiences that facilitate achieving 21st-century skills, one of which is creativity. This study aims to reveal research trends and future work related to creativity at the university level. The method used is a preferred reporting item for systematic review and meta-analysis protocols (PRISMA-P) and bibliometric analysis of the scopus database using vosviewer software. The author selected 778 documents that were considered relevant from English-language journal articles through a selection process. The results show that research topics related to creativity in higher education are still emerging and increasing. The results of the bibliometric analysis using the co-occurrence type of analysis show that there are several dominant keywords outside the search query, including human (36), engineering education (35), critical thinking (31), innovation (28), education for sustainable development (26), and project-based learning (21). Through network visualization analysis, information on the relationship between keywords and the strength of their relationship is obtained. The visualization of overlays shows several topics that are still growing and deserve to be researched, such as entrepreneurs, virtual reality, self-efficacy, etc. Through the help of the openrefine software, the author can find several future works related to specific issues. Several new keywords for future research can be determined. This study concludes that bibliometric analysis through vosviewer has successfully demonstrated trends and future work for creativity in higher education